1996
DOI: 10.1111/j.1528-1157.1996.tb00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Vigabatrin May Mimic α‐Aminoadipic Aciduria

Abstract: The concentrations of AAA in these VGB-treated children were as high as the concentrations found in the inherited metabolic disease, AAAuria. This could lead to incorrect diagnosis and to inappropriate genetic counseling. Thus whenever a genetic metabolic disease is suspected, amino acid chromatography testing should be performed before initiation of treatment with VGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…This value represents a 24-fold increase compared to the basal AAA values seen at zero time point that was estimated at approximately 3 μM. This value is similar to the 4 μM basal AAA concentration found in normal mouse plasma, as reported in the mouse multiple tissue metabolome database (MMMDB) (Sugimoto et al 2012 ) and in the human metabolome database (HMDB 2.0) (Vallat et al 1996 ; Wishart et al 2013 ) These results suggest that lysine is rapidly oxidized to AAA reaching a maximum within the first 2 h after lysine administration. Four to 6 h following IP lysine injection, AAA returned to concentrations that were not statistically different from that observed for zero time point.…”
Section: Resultssupporting
confidence: 82%
“…This value represents a 24-fold increase compared to the basal AAA values seen at zero time point that was estimated at approximately 3 μM. This value is similar to the 4 μM basal AAA concentration found in normal mouse plasma, as reported in the mouse multiple tissue metabolome database (MMMDB) (Sugimoto et al 2012 ) and in the human metabolome database (HMDB 2.0) (Vallat et al 1996 ; Wishart et al 2013 ) These results suggest that lysine is rapidly oxidized to AAA reaching a maximum within the first 2 h after lysine administration. Four to 6 h following IP lysine injection, AAA returned to concentrations that were not statistically different from that observed for zero time point.…”
Section: Resultssupporting
confidence: 82%
“…37 Furthermore, AAA levels were reported to increase in the plasma and urine of epileptic patients under VGB therapy. 38 AAA is long known to be a gliotoxin that affects Müller glial cells, 39 leading to an upregulation of GFAP and secondarily to photoreceptor dysmorphogenesis. 40 The involvement of AAA gliotoxicity in VGB-induced visual field constriction is further supported by the histological similarities between AAA-treated developing retina 41 and retina of VGB-treated animals.…”
Section: Fig 6 Ultrastructural Alterations Of Photoreceptors and Retmentioning
confidence: 99%
“…In addition, urine amino acid analysis revealed marked excretion of α-aminoadipic acid and β-alanine, indicative of vigabatrin therapy. 103,104 Further inquiry revealed that the patient had indeed received VPA (110mg/day) and vigabatrin (625mg/day) at the time of sampling.…”
mentioning
confidence: 99%